PENERAPAN ALAT PERAGA TORSO UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V A PADA PEMBELAJARAN IPAS DI SD SWASTA TIGA HATI KEPENUHAN HULU - Nur Alifia Sabri; Eni Marta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve the learning outcomes of fifth-grade students in class V A at Tiga Hati Kepenuhan Hulu Private Elementary School in the IPAS ( Science and Social Studies ) Subject by using a torso as an instructional tool. The research was prompted by low student performance, where only 21% of students met the learning objective ( scoring 66% - 85% ), while 79% did not. A lack of student enthusiasm and active participation, along with monotonous and unvaried teaching methods,resulted in passive and bored students. Additionally, the teacher’s use of instructional media was not optimal. This study utilizes a Classroom Action Research (CAR) approach, conducted in two cycles, with stages of planning, implementation, observation and reflection . the subjects were 29 fifth-grade students, consisting of 19 boys and 10 girls. Data was collected trough observation to asses student activity and test to measure learning outcomes. The findings of this research are expected to addres the identified issues by increasing student enthusiasm and mproving their evaluation scores.